Composite slow-release oxygen particle with multi-layer core-shell structure and preparation method of composite slow-release oxygen particle

By combining the multi-layer core-shell structure with the combination of the outer porous adsorption material and the catalytic functional material, the problem of low utilization of adsorbent materials in the prior art is solved, and the efficient removal of ammonia nitrogen and total phosphorus in water is achieved. , forming a local hyperoxygen environment and enhancing the effect of bottom mud restoration.

CN119240918AActive Publication Date: 2025-01-03CCCC SHANGHAI DREDGING CO LTD

Patent Information

Application Number
CN202410815489.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-06-24
Publication Date
2025-01-03
Estimated Expiration
2044-06-24

AI Technical Summary

Technical Problem

After the porous adsorption materials in existing sustained-release oxygen agents are mixed and embedded with calcium peroxide, the inner layer is difficult to play an adsorption role after the surface is adsorbed and saturated, resulting in low adsorption utilization and poor removal of pollutants such as ammonia nitrogen and total phosphorus in water. good.

Method used

The multi-layer core-shell structure composite sustained-release oxygen particles, including high-density inorganic microsphere weight-enhancing core, oxygen-release intermediate layer and outer shell layer. The outer layer contains porous adsorption materials and catalytic functional materials to ensure that the adsorbent material plays its maximum role in the outer layer. And achieve sustained release by physically cross-linking the PVA envelope.

Benefits of technology

Improve the removal efficiency of ammonia nitrogen and total phosphorus in water, form local high oxygen conditions, enhance the aerobic degradation of pollutants, and the outer PVA is insoluble in water to avoid pollution, and the particles can quickly settle to the bottom sludge, fully exert their full play. Repair effect.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention provides a multi-layer core-shell structure composite slow-release oxygen particle and a preparation method thereof. The multi-layer core-shell structure composite slow-release oxygen particle comprises a weight-increasing inner core, an oxygen-release middle layer and a functional surface layer. The weight increasing inner core is a high-density inorganic microsphere which is selected from one or more of alumina microspheres and silica microspheres, the weight increasing inner core comprises a binder and calcium peroxide and has a long-acting oxygen slow-release function, and the binder is selected from one of sodium alginate, xanthan gum and guar gum; the shell layer comprises a binder, a porous adsorption material and a catalytic functional material, the binder is physical crosslinking PVA, the adsorption functional material is selected from one or more of charcoal powder, zeolite powder, diatomite and attapulgite, and the catalytic functional material is selected from one or more of iron carbon powder, nano iron powder and pyrite powder.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of riverbed sediment treatment, and in particular to a multi-layer core-shell structure composite slow-release oxygen particle and a preparation method thereof. Background Art

[0002] Oxygenation is a common method in riverbed sediment management. Its main principle is to improve water quality by increasing the dissolved oxygen concentration in the water overlying the sediment and promoting the biochemical degradation and decomposition of various pollutants by aerobic microorganisms. Adding oxygen-releasing agents is one of the commonly used oxygenation methods. When oxygen-releasing agents are added to the sediment, the oxygen produced can directly act on various sediments to create an aerobic environment. The oxygen bubbles produced are small and can fully contact the sediment and the overlying water during the diffusion process, maximizing the role of oxygenation in repairing water quality. Oxygen-releasing agents are easy to add and have low construction and operation costs. It is more convenient to use this method for river water restoration.

[0003] Calcium peroxide has a low oxygen release rate and a long sustained release time, and has a high oxygen content and low cost, so it is the most commonly used oxygen release agent material. However, calcium peroxide is generally in powder form, and when it is put into water, it will fully contact and react with water, resulting in excessive initial oxygen release, exceeding the saturated dissolved oxygen content of water and the requirements for oxidative degradation of pollutants. The oxygen release lacks sustainability, resulting in the need for multiple excessive additions, so slow-release technology is needed to control its oxygen release rate.

[0004] At present, the common method for preparing slow-release oxygen agents is the embedding method, that is, embedding calcium peroxide through different carriers. Common embedding carriers include cement, bentonite, sodium alginate, sodium humate, polyhydroxyalkanoate (PHA), polyvinyl alcohol (PVA), etc. In addition, porous adsorption materials such as activated carbon are usually added to embed together with calcium peroxide. Porous adsorption materials can adsorb various pollutants and improve the repair effect on water quality. However, after the porous adsorption materials are mixed and embedded with calcium peroxide, in fact, only the porous materials on the surface have a high-efficiency adsorption effect. When the surface adsorption is saturated, the inner layer can hardly play an adsorption role, resulting in limited actual adsorption, low utilization rate of the embedded porous adsorption materials, and poor removal effect on pollutants such as ammonia nitrogen and total phosphorus in water. Summary of the invention

[0005] In order to solve the above problems existing in the prior art, the purpose of the present invention is to provide a multi-layer core-shell structure composite slow-release oxygen particle and a preparation method thereof, so as to overcome the above shortcomings and deficiencies existing in the prior art.

[0006] To achieve the above object, the present invention adopts the following technical solution:

[0007] A multi-layer core-shell structure composite slow-release oxygen particle comprises a three-layer structure of a weight-increasing core, an oxygen-releasing middle layer and an outer shell layer from the inside to the outside.

[0008] Optionally, the multi-layer core-shell structure composite slow-release oxygen particles have a diameter of 8-20 mm.

[0009] Optionally, the weight-added core is a high-density inorganic microsphere, and the high-density inorganic microsphere is selected from one or more of alumina microspheres and silica microspheres, and / or

[0010] The diameter of the high-density inorganic microspheres is 1-5 mm, more preferably 3-4 mm.

[0011] Optionally, the oxygen-releasing intermediate layer has a thickness of 5-10 mm, more preferably 6-8 mm.

[0012] Optionally, the oxygen-releasing intermediate layer comprises a binder and calcium peroxide, wherein the binder is selected from one of sodium alginate, xanthan gum and guar gum.

[0013] Optionally, the components of the outer shell layer include an outer layer binder, a porous adsorption material and a catalytic functional material, wherein the outer layer binder is physically cross-linked PVA, the adsorption functional material is selected from one or more of biochar powder, zeolite powder, diatomaceous earth, and attapulgite, and the catalytic functional material is selected from one or more of iron-carbon powder, nano iron powder, and pyrite powder.

[0014] Optionally, the outer shell layer has a thickness of 1-5 mm, and more preferably has a thickness of 2-3 mm.

[0015] The present invention also provides a method for preparing multi-layer core-shell structure composite slow-release oxygen particles, comprising the following steps:

[0016] Alumina and / or silica microspheres are used as weight-increasing cores, together with an oxygen-releasing binder and powdered calcium peroxide, and added into a disc granulator. The disc is tilted at an angle of 45-55° and rotated at a speed of 32-45 rpm. Water is sprayed on the surface of the material. The granulation time is 10-30 minutes to obtain two-layer core-shell structure particles.

[0017] The PVA particles are added into deionized water at 80-95°C to dissolve to prepare a PVA aqueous solution, wherein the concentration of the aqueous solution is 5-15wt%;

[0018] The two-layer core-shell structure particles, porous adsorption material and catalytic functional material are added into a disc granulator, the disc inclination angle is 45-55°, the rotation speed is 32-45rpm, the PVA aqueous solution is sprayed on the surface of the material, and the granulation time is 5-20 minutes to obtain three-layer core-shell structure slow-release oxygen particles;

[0019] The three-layer core-shell structure slow-release oxygen particles are frozen at -20°C for 8-12 hours, thawed for 4 hours, and repeated freezing and thawing for 2-4 times, and then dried at 60°C-70°C for 5-10 hours to obtain a finished product.

[0020] Optionally, the diameter of the multi-layer core-shell structure composite slow-release oxygen particles is 8-20 mm, and / or

[0021] The diameter of the alumina and / or silica microspheres is 1-5 mm, more preferably 3-4 mm.

[0022] Optionally, the binder is selected from sodium alginate, xanthan gum, and guar gum.

[0023] Due to the adoption of the above technical solution, the present invention has the following beneficial effects:

[0024] 1. Strong adsorption function, high efficiency in removing ammonia nitrogen and total phosphorus in water. Due to the multi-layer structure of this product, the oxygen-releasing material calcium peroxide and the adsorption material in the product are not directly mixed together, and the adsorption material is in the outermost layer of the particles, so it can maximize its adsorption function. After the product particles are put into the water body, they can effectively adsorb ammonia nitrogen, organic pollutants, etc. in the water body. At the same time, water can enter the middle layer through the outer layer to react with calcium peroxide, and the generated oxygen is easily retained by the porous adsorption material in the outer layer, forming aerobic conditions with high local concentrations, thereby forming a micro-biochemical reactor, so that the adsorbed ammonia nitrogen, organic pollutants, etc. can be eliminated through aerobic reactions, thereby achieving the purpose of efficiently removing pollutants such as ammonia nitrogen and total phosphorus.

[0025] 2. The outer layer of adhesive is a physically cross-linked PVA coating layer, which can play a role in slow release of oxygen, and the cross-linked PVA is insoluble in water, so it will not cause organic matter to dissolve and cause pollution.

[0026] 3. Adding a weighted core can quickly settle to the bottom mud and is not easily washed away by water, so it can fully play the role of bottom mud repair. DETAILED DESCRIPTION

[0027] The present invention will be further described below with reference to the embodiments.

[0028] Embodiment 1:

[0029] 4 kg of calcium peroxide and 80 g of food-grade sodium alginate powder were stirred and mixed evenly, and then added into a disc granulator together with 500 g of alumina microspheres with a diameter of 3 mm. The disc was tilted at 52° and rotated at 36 rpm. 650 g of water was sprayed on the surface of the material. The granulation time was 20 minutes to obtain two-layer core-shell structure particles with a diameter of about 8 mm.

[0030] PVA particles were added to deionized water at 80-95°C to prepare an 8wt% PVA aqueous solution. 1kg of biochar and 0.5kg of pyrite were stirred and evenly mixed, and then added into a disc granulator together with the aforementioned two-layer core-shell structure particles. The disc was tilted at 52° and rotated at 32rpm. 150g of 8wt% PVA aqueous solution was sprayed on the surface of the material. The granulation time was 5 minutes to obtain three-layer core-shell structure particles with a diameter of about 11mm.

[0031] The obtained particles were immediately frozen at -20°C for 8 hours, thawed for 4 hours, and repeated three times, and then dried at 60°C for 8 hours to obtain a finished product.

[0032] Embodiment 2:

[0033] 5 kg of calcium peroxide and 100 g of food-grade sodium alginate powder were stirred and mixed evenly, and then added into a disc granulator together with 500 g of alumina microspheres with a diameter of 5 mm. The disc inclination angle was 52°, the rotation speed was 36 rpm, 800 g of water was sprayed on the surface of the material, and the granulation time was 25 minutes to obtain two-layer core-shell structure particles with a diameter of about 11 mm.

[0034] PVA particles were added to deionized water at 80-95°C to prepare an 8wt% PVA aqueous solution. 1kg of biochar and 0.5kg of pyrite were stirred and evenly mixed, and then added into a disc granulator together with the aforementioned two-layer core-shell structure particles. The disc inclination angle was 52° and the rotation speed was 32rpm. 150g of 8wt% PVA aqueous solution was sprayed on the surface of the material. The granulation time was 5 minutes to obtain three-layer core-shell structure particles with a diameter of about 13mm.

[0035] The obtained particles were immediately frozen at -20°C for 8 hours, thawed for 4 hours, and repeated three times, and then dried at 60°C for 8 hours to obtain a finished product.

[0036] Embodiment 3:

[0037] 5 kg of calcium peroxide and 100 g of food-grade sodium alginate powder were stirred and mixed evenly, and then added into a disc granulator together with 500 g of alumina microspheres with a diameter of 4 mm. The disc was tilted at 52° and rotated at 36 rpm. 800 g of water was sprayed on the surface of the material. The granulation time was 25 minutes to obtain two-layer core-shell structure particles with a diameter of about 10 mm.

[0038] PVA particles are added to deionized water at 80-95°C to dissolve in a 10wt% PVA aqueous solution. 1kg of biochar and 0.5kg of pyrite are stirred and evenly mixed, and then added into a disc granulator together with the aforementioned two-layer core-shell structure particles. The disc inclination angle is 52°, the rotation speed is 32rpm, 130g of 10wt% PVA aqueous solution is sprayed on the surface of the material, and the granulation time is 6 minutes to obtain three-layer core-shell structure particles with a diameter of about 12mm.

[0039] The obtained particles were immediately frozen at -20°C for 8 hours, thawed for 4 hours, and repeated three times, and then dried at 60°C for 8 hours to obtain a finished product.

[0040] Embodiment 4:

[0041] 5 kg of calcium peroxide and 100 g of food-grade sodium alginate powder were stirred and mixed evenly, and then added into a disc granulator together with 500 g of alumina microspheres with a diameter of 4 mm. The disc was tilted at 52° and rotated at 36 rpm. 800 g of water was sprayed on the surface of the material. The granulation time was 25 minutes to obtain two-layer core-shell structure particles with a diameter of about 10 mm.

[0042] PVA particles are added to deionized water at 80-95°C to dissolve in a 10wt% PVA aqueous solution, 1kg 60-mesh zeolite powder and 0.5kg pyrite are stirred and mixed evenly, and then added into a disc granulator together with the aforementioned two-layer core-shell structure particles. The disc has an inclination angle of 52° and a rotation speed of 32rpm. 120g of a 10wt% PVA aqueous solution is sprayed on the surface of the material. The granulation time is 6 minutes to obtain three-layer core-shell structure particles with a diameter of about 12mm.

[0043] The obtained particles were immediately frozen at -20°C for 8 hours, thawed for 4 hours, and repeated three times, and then dried at 60°C for 8 hours to obtain a finished product.

[0044] Embodiment 5:

[0045] 5 kg of calcium peroxide and 100 g of food-grade sodium alginate powder were stirred and mixed evenly, and then added into a disc granulator together with 500 g of alumina microspheres with a diameter of 4 mm. The disc was tilted at 52° and rotated at 36 rpm. 800 g of water was sprayed on the surface of the material. The granulation time was 25 minutes to obtain two-layer core-shell structure particles with a diameter of about 10 mm.

[0046] PVA particles are added to deionized water at 80-95°C to dissolve in a 10wt% PVA aqueous solution, 1kg 60-mesh diatomaceous earth and 0.5kg nano iron powder are stirred and mixed evenly, and then added into a disc granulator together with the aforementioned two-layer core-shell structure particles. The disc inclination angle is 52°, the rotation speed is 32rpm, 120g of 10wt% PVA aqueous solution is sprayed on the surface of the material, and the granulation time is 6 minutes to obtain three-layer core-shell structure particles with a diameter of about 12mm.

[0047] The obtained particles were immediately frozen at -20°C for 8 hours, thawed for 4 hours, and repeated three times, and then dried at 60°C for 8 hours to obtain a finished product.

[0048] Comparison example:

[0049] PVA particles were added into deionized water at 80-95° C. to dissolve and prepare a 10 wt % PVA aqueous solution.

[0050] 5 kg of calcium peroxide, 100 g of food-grade sodium alginate powder, 1 kg of biochar and 0.5 kg of pyrite were stirred and mixed evenly, and then added into a disc granulator together with 500 g of alumina microspheres with a diameter of 4 mm. The disc inclination angle was 52° and the rotation speed was 36 rpm. 800 g of 10 wt% PVA aqueous solution was sprayed on the surface of the material. The granulation time was 25 minutes to obtain two-layer core-shell structure particles with a diameter of about 12 mm.

[0051] The obtained particles were immediately frozen at -20°C for 8 hours, thawed for 4 hours, and repeated three times, and then dried at 60°C for 8 hours to obtain a finished product.

[0052] Test results

[0053] The sediment remediation experiments of Examples 1-5 and the control example were conducted in a square open water tank with a height of 1m, in which a 300mm thick sediment was laid and the overlying water body height was 400mm. The above-mentioned slow-release oxygen particles were added at a rate of 1kg / m 2 The dosage is added to the upper surface of the sediment, and then the overlying water samples are taken regularly to test various water quality indicators such as ammonia nitrogen and total phosphorus. Ammonia nitrogen is determined by Nessler's reagent spectrophotometry, and total phosphorus is determined by ultraviolet spectrophotometry. The initial ammonia nitrogen and total phosphorus concentrations of the overlying water of the sediment are 21.7 mg / L and 2.18 mg / L, respectively. Ten days after the addition of the slow-release oxygen particles, the ammonia nitrogen and total phosphorus removal rates of the embodiment are higher than those of the control example, as shown in the following table:

[0054]

[0055] The technical solution of the present invention has the following beneficial effects:

[0056] 1. Strong adsorption function, high efficiency in removing ammonia nitrogen and total phosphorus in water. Due to the multi-layer structure of this product, the oxygen-releasing material calcium peroxide and the adsorption material in the product are not directly mixed together, and the adsorption material is in the outermost layer of the particles, so it can maximize its adsorption function. After the product particles are put into the water body, they can effectively adsorb ammonia nitrogen, organic pollutants, etc. in the water body. At the same time, water can enter the middle layer through the outer layer to react with calcium peroxide, and the generated oxygen is easily retained by the porous adsorption material in the outer layer, forming aerobic conditions with high local concentrations, thereby forming a micro-biochemical reactor, so that the adsorbed ammonia nitrogen, organic pollutants, etc. can be eliminated through aerobic reactions, thereby achieving the purpose of efficiently removing pollutants such as ammonia nitrogen and total phosphorus.

[0057] 2. The outer layer of adhesive is a physically cross-linked PVA coating layer, which can play a role in slow release of oxygen, and the cross-linked PVA is insoluble in water, so it will not cause organic matter to dissolve and cause pollution.

[0058] 3. Adding a weighted core can quickly settle to the bottom mud and is not easily washed away by water, so it can fully play the role of bottom mud repair.

[0059] The specific implementation modes of the present invention are described above, but the present invention is not limited thereto. The present invention can also have various changes without departing from the purpose of the present invention.

Claims

1. A multi-layer core-shell structure composite slow-release oxygen granule, characterized in that: It includes a three-layer structure from the inside to the outside: a weighted inner core, an oxygen-releasing middle layer and an outer shell layer.

2. The multi-layer core-shell structure composite slow-release oxygen particles according to claim 1, characterized in that: The multi-layer core-shell structure composite slow-release oxygen particles have a diameter of 8-20 mm.

3. The multi-layer core-shell structure composite slow-release oxygen particles according to claim 1, characterized in that: The weighted core is a high-density inorganic microsphere, wherein the high-density inorganic microsphere is selected from one or more of alumina microspheres and silica microspheres, and / or The diameter of the high-density inorganic microspheres is 1-5 mm, more preferably 3-4 mm.

4. The multi-layer core-shell structure composite slow-release oxygen particles according to claim 1, characterized in that: The thickness of the oxygen-releasing intermediate layer is 5-10 mm, more preferably 6-8 mm.

5. The multi-layer core-shell structure composite slow-release oxygen particles according to claim 1 or 4, characterized in that: The oxygen-releasing middle layer comprises a binder and calcium peroxide, wherein the binder is selected from one of sodium alginate, xanthan gum and guar gum.

6. The multi-layer core-shell structure composite slow-release oxygen particles according to claim 1, characterized in that: The components of the outer shell layer include an outer layer binder, a porous adsorption material and a catalytic functional material, wherein the outer layer binder is physically cross-linked PVA, the adsorption functional material is selected from one or more of biochar powder, zeolite powder, diatomaceous earth, and attapulgite, and the catalytic functional material is selected from one or more of iron-carbon powder, nano iron powder, and pyrite powder.

7. The multi-layer core-shell structure composite slow-release oxygen particles according to claim 1 or 6, characterized in that: The thickness of the outer shell layer is 1-5 mm, and more preferably 2-3 mm.

8. A method for preparing multi-layer core-shell structure composite slow-release oxygen particles, characterized in that: The following steps are involved: Alumina and / or silica microspheres are used as weight-increasing cores, and are added into a disc granulator together with a binder and powdered calcium peroxide. The disc is tilted at an angle of 45-55° and rotated at a speed of 32-45 rpm. Water is sprayed on the surface of the material. The granulation time is 10-30 minutes to obtain two-layer core-shell structure particles. The PVA particles are added into deionized water at 80-95°C to dissolve to prepare a PVA aqueous solution, wherein the concentration of the aqueous solution is 5-15wt%; The two-layer core-shell structure particles, porous adsorption material and catalytic functional material are added into a disc granulator, the disc inclination angle is 45-55°, the rotation speed is 32-45rpm, the PVA aqueous solution is sprayed on the surface of the material, and the granulation time is 5-20 minutes to obtain three-layer core-shell structure slow-release oxygen particles; The three-layer core-shell structure slow-release oxygen particles are frozen at -20°C for 8-12 hours, thawed for 4 hours, and frozen and thawed repeatedly for 2-4 times, and then dried at 60°C-70°C for 5-10 hours to obtain a finished product.

9. The method for preparing the multi-layer core-shell structure composite slow-release oxygen particles according to claim 8, characterized in that: The diameter of the multi-layer core-shell structure composite slow-release oxygen particles is 8-20 mm, and / or The diameter of the alumina and / or silica microspheres is 1-5 mm, more preferably 3-4 mm.

10. The method for preparing multi-layer core-shell structure composite slow-release oxygen particles according to claim 8, characterized in that: The binder is selected from one of sodium alginate, xanthan gum and guar gum.

Citation Information

Patent Citations

  • Spherical SiO2-based adsorbent adopting core-shell structure as well as preparation method and application of adsorbent

    CN104801267A

  • Infiltration reaction wall composite material for underwater polyaromatic hydrocarbon pollution remediation as well as preparation method and application method of Infiltration reaction wall composite material

    CN105293683A

  • Preparation method of multifunctional polyvinyl alcohol hydrogel material for ecological restoration of water body

    CN114177845A

Cited By

  • Centralized ecological restoration method for drinking water source land

    CN120622684A